PKMζ is necessary and sufficient for synaptic clustering of PSD-95 - Shao, Charles Y. (2011)
The persistent activity of protein kinase Mzeta (PKMζ), a brain-specific, constitutively active protein kinase C isoform, maintains synaptic long-term potentiation (LTP). Structural remodeling of the postsynaptic density is believed to contribute to the expression of LTP. We therefore examined the role of PKMζ in reconfiguring PSD-95, the major postsynaptic scaffolding protein at excitatory synapses. In primary cultures of hippocampal neurons, PKMζ activity was critical for increasing the size of PSD-95 clusters during chemical LTP (cLTP). Increasing PKMζ activity by overexpressing the kinase in hippocampal neurons was sufficient to increase PSD-95 cluster size, spine size, and postsynaptic AMPAR subunit GluA2. Overexpression of an inactive mutant of PKMζ did not increase PSD-95 clustering, and applications of the ζ-pseudosubstrate inhibitor ZIP reversed the PKMζ-mediated increases in PSD-95 clustering, indicating that the activity of PKMζ is necessary to induce and maintain the increased size of PSD-95 clusters. Thus the persistent activity of PKMζ is both necessary and sufficient for maintaining increases of PSD-95 clusters, providing a unified mechanism for long-term functional and structural modifications of synapses.